Pemberian Posisi Semi Fowler Untuk Meningkatkan Saturasi Oksigen pada Pasien CHF (Congestive Heart Failure) di Ruang ICU RSUD Pandanarang Boyolali - Putri Sinta, Cindyana; Husain, Fida'; Widodo, Panggah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The prevalence of heart failure in Indonesia based on a doctor's diagnosis is estimated at 1.5% or around 29,550 people. Congestive heart failure is caused by interference and blockage of blood flow in the heart so that it will cause signs and symptoms of heart failure in the systemic circulation and pulmonary circulation such as pain, shortness of breath. The problem that often occurs in patients with congestive heart failure is shortness of breath, so non-pharmacological management is needed, one of which is semi-Fowler's position. To find out the results of applying semi-Fowler's position to congestive heart failure patients. The application was carried out using a case study descriptive method to 2 respondents with a diagnosis of Congestive Heart Failure carried out 3 days for 1x a day for 15 minutes. Based on the results of the implementation that has been done, there is an increase in oxygen saturation in congestive heart failure patients by 3-4%. Giving a semi-fowler position can be used as a non-pharmacological technique or independent intervention in patients with congestive heart failure.